2022
DOI: 10.17478/jegys.1085660
|View full text |Cite
|
Sign up to set email alerts
|

Exploring challenges experienced by foundation phase teachers in using technology for teaching and learning : a South African case study

Abstract: The Department of Education introduced the policy on e-Education in 2004, encouraging all teachers to implement technology for teaching and learning. Despite this encouragement, most South African teachers are experiencing many challenges to effectively use technology for teaching and learning in the foundation phase. This study explored the challenges experienced by foundation phase teachers in using technology for teaching and learning in two schools in one district in Gauteng Province: South Africa. The Tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…These techniques included textbased interviews, observation schedules, participants' reflective journals, and documentation. Venketsamy and Hu [29] concurred with Creswell [30] that the adoption of diverse data collection methods strengthens the trustworthiness of the findings. The text-based interviews took place between March 2022 and April 2022.…”
Section: Methodsmentioning
confidence: 62%
“…These techniques included textbased interviews, observation schedules, participants' reflective journals, and documentation. Venketsamy and Hu [29] concurred with Creswell [30] that the adoption of diverse data collection methods strengthens the trustworthiness of the findings. The text-based interviews took place between March 2022 and April 2022.…”
Section: Methodsmentioning
confidence: 62%
“…Although the local literature has separately explored the teaching and implementation of RE (Chidester, 2006;Ntho-Ntho & Nieuwenhuis, 2016a, 2016bRoux, 2013) and CSE in schools (Francis, 2017c;Ngabaza & Shefer, 2019;Venketsamy, 2018), the problem is that there are no available studies which have explored the intersections of both polices together.…”
Section: Implementing Educational Policy Protecting the Rights Of Rel...mentioning
confidence: 99%
“…According to Francis (2011), it is not uncommon for the teaching about gender and sexuality diversity to be disregarded from CSE curriculum as these themes may conflict with teachers' religious and cultural beliefs. For instance, Venketsamy's (2018) investigation into the challenges experienced by South African black male and female teachers teaching CSE revealed that these teachers failed to teach on themes such as same-sex relationships based on conflicting values with their cultural and religious beliefs. Similarly, the interviewed learners in Mayeza and Vincent (2019) study demanded more knowledge about dating and same-sex relationships.…”
Section: South African Schools' Comparative Responses To the Implemen...mentioning
confidence: 99%
“…While Simelane, Blignaut and Van Ryneveld (2007) conducted a study on preparing lecturers to integrate educational technology into their teaching and learning practices. Venketsamy and Zijing (2022) explored the challenges experienced by the foundation phase teachers in using technology for teaching and learning. Hence, all these studies focused on strategies far beyond the scope of the innovative strategies for integrating technologies.…”
Section: Introductionmentioning
confidence: 99%